AN OPERATIONS RESEARCH AND SIMULATION - de Jongh, E; Botha, G J (The South African Journal of Industrial Engineering, 2013)
This paper relates to a company that produces washing powders. The focus is on improving the efficiency of gas usage (per unit of powder produced) in the furnace that produces hot air. This hot air is an integral part of washing powder production: it dries the viscous slurry and transforms it into the base powder used in all washing powders. The cost of gas is the factory